2021
DOI: 10.3174/ajnr.a7278
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of the Olfactory System in COVID-19: An MR Imaging Study

Abstract: BACKGROUND AND PURPOSE: Anosmia or hyposmia, often accompanied by changes in taste, is recognized as a common symptom that can assist in the diagnosis of coronavirus disease 2019 . The pathogenesis of olfactory dysfunction in COVID-19is not yet fully understood. MR imaging represents a useful anatomic imaging method for the evaluation of olfactory dysfunction associated with varying etiologies, including viral infection, trauma, and neurodegenerative processes. This case-control study was conducted to compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 35 publications
(29 reference statements)
2
21
0
Order By: Relevance
“…The summary of demographic and methodologic characteristics for each included study can be found in Table 1 . The most frequently reported structural measurements were right OB volume and left OB volume with six studies [ 4 , 33 – 35 , 37 , 39 ], right OS depth and left OS depth with five studies [ 4 , 33 , 34 , 37 , 39 ], and signal intensity of OB with three studies [ 31 , 38 , 39 ]. Quality assessment of the included studies by the NOS scale indicated a fair status for most of the articles, with the total score ranging from two to seven (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The summary of demographic and methodologic characteristics for each included study can be found in Table 1 . The most frequently reported structural measurements were right OB volume and left OB volume with six studies [ 4 , 33 – 35 , 37 , 39 ], right OS depth and left OS depth with five studies [ 4 , 33 , 34 , 37 , 39 ], and signal intensity of OB with three studies [ 31 , 38 , 39 ]. Quality assessment of the included studies by the NOS scale indicated a fair status for most of the articles, with the total score ranging from two to seven (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mean right and mean left OS depths have been evaluated in five studies with pooled population of 436 individuals (155 COVID-19 cases and 281 non-COVID-19 controls) [ 4 , 33 , 34 , 37 , 39 ]. There was no statistically significant difference in right OS depth (SMD, − 0.237; 95% CI, − 0.697 to 0.223; P = 0.3122; I 2 = 80.12%; P Q = 0.005; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In current practice, olfactory imaging is not routinely performed for COVID‐19 patients with OD. However, neuroimaging abnormalities related to COVID‐19‐associated OD have been gaining attention, including abnormalities of the olfactory bulb, olfactory sulcus, olfactory cleft, and olfactory tract on imaging 14,15 . These imaging findings may shed light on the mechanisms underlying COVID‐19‐associated OD, 16 offering insight into the route of entry of the SARS‐CoV‐2 virus, and involvement of anatomical structures in the brain and olfactory pathways 17 .…”
Section: Introductionmentioning
confidence: 99%
“…However, neuroimaging abnormalities related to COVID‐19‐associated OD have been gaining attention, including abnormalities of the olfactory bulb, olfactory sulcus, olfactory cleft, and olfactory tract on imaging. 14 , 15 These imaging findings may shed light on the mechanisms underlying COVID‐19‐associated OD, 16 offering insight into the route of entry of the SARS‐CoV‐2 virus, and involvement of anatomical structures in the brain and olfactory pathways. 17 Moreover, knowledge gained from such data may enable clinicians to more accurately predict the clinical course, and develop targeted interventions to treat COVID‐19‐associated OD.…”
Section: Introductionmentioning
confidence: 99%